Efikasi Insektisida Berbagai Ekstrak Etanol Daun Tumbuhan Terhadap Larva Aedes Aegypti dan Anapheles Acanitus di Laboratorium - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Environment sanitation is part of general public health including work principles for destroyed environmental factors that cause disease. Environment sanitation include water, food, air sanitation, vector and rodent animal control. Plants as a sources of good insecticide's materials be developed as vector control, because they were safe, degradable and environment friendly. The aim of this experiment was to study the lethal capacity of insecticide plants, establish relation between concentration and exposure time also comparative residue's effect of extract ethanol from A.conyzoides, D. metel, M. azedarach, N. tabacum, P. edule, and D. elliptica toward mortality Ae. aegypti and An. aconitus larvaes. This research was an experimental study with Post Test Only Control Group Design approach. Population in this research were larvaes of Ae. aegypti and An. aconitus. There were colonyzed in Vector and Reservoir Control Research Unit (VRCRU) laboratory at Salatiga. Samples of this research were consist 25 3rd Instar larvaes with nine concentration and three repetitions. Material of this research were extract ethanol from six leaves plants. Lethal Concentration (LC95) of the larvaes analysed by Probit Analysis (Finney D.J., 1971). The larvacide activity of A.conyzoides, D.metel, M.azedarach, N.tabacum, P.edule Reinw and D. elliptica extract against larvae Ae. aegypt and An. aconitus were 2,81 %v/v